Characteristics and driving mechanisms of vegetation phenology variations in the Bosten Lake Basin, Xinjiang, China - Kunyu Li; Xuemei Wang; Zitai Liu; Cong Xue (PLoS ONE, 2025)
Vegetation phenology functions as a highly sensitive biological metric for delineating the growth state of vegetation and mirroring environmental alterations. The exploration of its spatiotemporal variations and driving forces constitutes a key area within contemporary global change research. Leveraging MODIS NDVI data spanning from 2001 to 2023, this research derived phenology parameters for the Bosten Lake Basin in Xinjiang, China. The Sen+Mann-Kendall approach was utilized to analyze vegetation phenology trends, and the partial least squares path model (PLS-PM) was applied to quantitatively disclose the direct and indirect influences of climate, terrain, soil, and human activities on phenology. The findings indicated that over the past 23 years, the start of growing season (SOS) in the Bosten Lake Basin was predominantly concentrated between the 120th and 150th days, and it progressively advanced from the western to the eastern part. The end of growing season (EOS) fluctuated between the 240th and 270th days and gradually postponed from west to east. The length of the growing season (LOS) is mainly between 105 and 140 days and gradually lengthens from west to east. In the past 23 years, SOS advanced at an average rate of 8.9 days per decade, EOS advanced by 1.7 days per decade, and LOS extended by an average of 7.2 days per decade. The phenological parameters of diverse vegetation types demonstrated marked disparities. Needleleaf forests and cultivated vegetation exhibited earlier SOS, later EOS, and longer LOS, whereas alpine vegetation had the shortest growing season, approximately 73 days. With the increase of elevation, SOS was significantly delayed, EOS was significantly advanced, and LOS was significantly shortened (p < 0.05 for all). The direct impacts of climatic factors on SOS, EOS, and LOS were significant (p < 0.01), with total impacts of 1.03, −0.94, and −1.00, respectively. Among these climatic factors, temperature and precipitation are the most representative variables reflecting the influence of climate on phenology. Altitude indirectly affects phenology through climate, soil conditions, and human activities. Understanding the phenological change characteristics and driving mechanisms in the Bosten Lake Basin provides a basis for clarifying the ecological environment evolution and climate response in arid regions of China.